The productive efficiency of rearing herds in Pastaza, Ecuador - Benítez, Diocles; Torres, Verena; Vargas, J. C.; Soria, Sandra (Cuban Journal of Agricultural Science, 2016)
in the rearing- fattening system in Pastaza province, located in the Ecuadorian Amazonia, a non-experimental design was used which controlled the effects of the climatic areas and height levels. For the information processing the Statistical Model of Impact Measuring (MEMI) was applied. It was found that the factors which determine the efficiency of meat production in cattle rearing were reproduction, land relief and looses in the herd, these factors explain 85.54% ofthe system accumulated variance. These factors are related with the productive process efficiency, relief characteristics, environmental degradation and animals looses. The rearing- fattening systems are classified in four groups, differentiated by the herd size which exploit, the relief where are located, the production process efficiency and the impact they have on the environment. The productive efficiency is low and it correspond with the widespread exploitation alternatives, which are not fit to the environment demands, and with the ability touse the land on which these production processes are developed. It is possible to implement sustainable alternatives of meat production from cattle rearing-fattening systems, if the production systems are fit to the environments demands where these systems are developed.Key words: animal husbandry, impact model, productive chain, Amazonia